Study on the Factors of Delay for New 3-Storey Building Project Owned by Road Transport Department (RTD) Muar - Anuar, Shahira; Tami, Hannifah (Recent Trends in Civil Engineering and Built Environment, 2021)
Construction delays are defined as work that is completed later than expected or according to the contract timeline. Construction delays can only be reduced by recognising the causes. The goals of the research were to determine the key causes of construction delays and how Public Work Department (PWD) acts to solve the delayed as authority based on standards and procedure. The purpose of this study is to present an evidence-based analysis of the construction project of Road Transport Department Malaysia (RTD) in Muar. An interview and a questionnaire survey were used to conduct this research. Based on a literature analysis, seven groups were identified as contributing to the cause of construction delays and the process and standard for PWD in handling delayed project. In conclusion, contractor-related delays were ranked as the most major causes of delays.